Hysteresis of MnFePSi Spherical Powder Ensembles Studied by Magneto‐Optical Imaging. Issue 2 (11th September 2017) - Funk, Alexander; Zeilinger, Michael; Dötz, Florian; Soldatov, Ivan; Schäfer, Rudolf; Waske, Anja
Abstract : Temperature‐dependent magneto‐optical imaging is applied to study the thermal hysteresis of magnetocaloric MnFePSi spherical powder‐packed beds across their magneto‐elastic transition. Cooling and heating imaging series are used to analyze the transition of such a complex powder ensemble. The magnetization versus temperature behavior reconstructed from these local measurements shows very good agreement with integral measurements of the magnetization of the whole packed bed. Hence, local magneto‐optical imaging measurements represent the ensemble behavior well if the number of measurements is large enough. Furthermore, we analyzed the Curie temperature ( T C ) distribution of layers with different T C values and observed that the spread of T C within one layer is larger than the spacing between different layers, leading to a gradual switching behavior of the layer ensemble. Additionally, high resolution light microscopy was applied to observe the transition of individual particles, and correlate it to the local magnetic measurements. Abstract : Temperature‐dependent magneto‐optical imaging is applied to study the thermal hysteresis of magnetocaloric MnFePSi spherical powder packed beds across their magneto‐elastic transition. Cooling and heating imaging series are used to analyze the transition of the Curie temperatures TC s show a spreading that is correlated to slightly different chemical compositions of the particles, defects, stresses or microstructural features.